Land use change and its effect on ecosystem services in an Oxisol of the eastern High Plains of meta department in Colombia - Moreno-Conn, Lina M.; Rodríguez-Hernandez, Nubia S.; Arguello, José Orlando; Gallo Gordillo, Oscar; Bernal-Riobo, Jaime H.; Arango, Miguel; Baquero, José E. (Frontiers in Environmental Science, 2022)
Eastern high plains in the Orinoquia region are considered the last agricultural frontier in Colombia. Soils, mainly from oxisol order, are naturally acidic and dense with high iron and aluminum content, low fertility, low organic matter, and highly fragile when subjected to intensive tillage. These conditions and changes in land use transforming large savanna areas into intensive agricultural systems make it necessary to use crop management strategies that allow this region's sustainable and competitive development. This research aimed to evaluate the impact of use and soil management in an oxisol of native savanna with the establishment of five productive systems (Annual crops rotation – Sugarcane; Annual crops rotation; Sugarcane; Permanent crop Rubber associated with a legume Desmodium ovalifollium as a cover crop; Pasture Brachiaria decumbens - Annual crops rotation and native savanna as control by conditioning the soil with two doses of dolomite lime and the incorporation of three tillage methods over five years on indicators associated with ecosystem services (ES), such as fertility, water regulation, macroinvertebrate diversity, climate control related to greenhouse gas emissions (GHG) and carbon stock. The Principal Components Analysis (PCA) constructed indicators of ecosystem services, adjusting values between 0.10 and 1.0. Physicochemical variables with the greatest statistical weight were identified for components 1 and 2 each year. The fertility indicator of the native savanna for year one had a low range with a value of 0.11 compared to the other systems (p ≤ 0.05). During the years two, three, and four, the soil fertility indicator was greater in the production system of pasture Brachiaria decumbens - Annual crop rotation (0.51) compared to the other systems due to relatively high soil concentrations of Ca and Mg. Edaphic macroinvertebrates biodiversity indicator was greater in the Pasture Brachiaria decumbens compared to other systems. The indicators evaluated in the present research made it possible to identify the positive and negative impact of the intervention of the native savanna with productive systems accompanied by agronomic practices that guarantee production.